The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00787-021-01813-7
|View full text |Cite
|
Sign up to set email alerts
|

Age at school entry and reported symptoms of attention-deficit/hyperactivity in first graders: results of the prospective cohort study ikidS

Abstract: Young age at school entry (ASE) is related to attention-deficit/hyperactivity disorder in higher grades. The reason for this association is unclear, but medical oversupply and stress-related factors are discussed. We aimed to investigate whether ASE is associated with reported symptoms of attention-deficit/hyperactivity (ADH) already in first grade. Data of a population-based prospective cohort study (N = 2003; Mainz-Bingen region; Rhineland-Palatinate; Germany) with baseline assessments prior to school entry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…In this hypothesis, ADHD is conceptualized as an individual deficit, but the RAE is blamed on an inadequate match between individual characteristics of the students and that of the school environment. This stress-related hypothesis was confirmed by the study of Diefenbach et al [ 34 ]: RAE was associated with ADHD-related behaviors at the end of the first grade but not at the beginning of the school year. However, this effect does not seem to endure over time because studies have shown that the RAE in ADHD is less common in adolescence and even disappears in adulthood [ 23 ].…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…In this hypothesis, ADHD is conceptualized as an individual deficit, but the RAE is blamed on an inadequate match between individual characteristics of the students and that of the school environment. This stress-related hypothesis was confirmed by the study of Diefenbach et al [ 34 ]: RAE was associated with ADHD-related behaviors at the end of the first grade but not at the beginning of the school year. However, this effect does not seem to endure over time because studies have shown that the RAE in ADHD is less common in adolescence and even disappears in adulthood [ 23 ].…”
Section: Introductionmentioning
confidence: 55%
“…We tested another hypothesis ( H4 ), which suggested that teachers were more likely to identify children having the double burden of being young in class and exhibiting ADHD behaviors because of their greater struggle in school. This hypothesis emphasized the importance of functional impairment as the main reason to seek medical care [ 17 , 34 ]. However, it could not be confirmed by our models, which were limited by the cross-sectional nature of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐two studies investigated the association between relative age and behaviour using questionnaires to assess internalizing and externalizing behaviours. The necessary information to obtain effect sizes was only available for ten studies (Broughton et al, 2022; Diefenbach et al, 2021; Goodman et al, 2003; Lien et al, 2005; Lincove & Painter, 2006; Price et al, 2017; Reijneveld et al, 2006; Wendt et al, 2018; Wienen et al, 2018; Wisniewski et al, 1995). These studies were included in a random effect meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%